Pharmacokinetic/Toxicity Properties of the New Anti-Staphylococcal Lead Compound SK-03-92 - William R. Schwan; Jill M. Kolesar; M. Shahjahan Kabir; Edmund J. Elder; Jeffrey B. Williams; Rachel Minerath; James M. Cook; Christopher M. Witzigmann; Aaron Monte; Tricia Flaherty (MDPI AG, 2015)
Because of the potential of a new anti-staphylococcal lead compound SK-03-92 as a topical antibiotic, a patch, or an orally active drug, we sought to determine its safety profile and oral bioavailability. SK-03-92 had a high IC50 (125 μg/mL) in vitro against several mammalian cell lines, and mice injected intraperiteonally at the highest dose did not exhibit gross toxicity (e.g., altered gait, ungroomed, significant weight loss). Single dose (100 μg/g) pharmacokinetic (PK) analysis with formulated SK-03-92 showed that peak plasma concentration (1.64 μg/mL) was achieved at 20-30 min. Oral relative bioavailability was 8%, and the drug half-life was 20-30 min, demonstrating that SK-03-92 is likely not a candidate for oral delivery. Five-day and two-week PK analyses demonstrated that SK-03-92 plasma levels were low. Multi-dose analysis showed no gross adverse effects to the mice and a SK-03-92 peak plasma concentration of 2.12 μg/mL with the presence of significant concentrations of breakdown products 15 min after dosing. SK-03-92 appeared to be very safe based on tissue culture and mouse gross toxicity determinations, but the peak plasma concentration suggests that a pro-drug of SK-03-92 or preparation of analogs of SK-03-92 with greater bioavailability and longer half-lives are warranted.